Genomic characterization and tissue tropism variations of two porcine delta coronavirus strains isolated in China - Guangli Hu; Yihui Huang; Zexin Chen; Rui Geng; Zhiqing Zhao; Ouyang Peng; Chuangchao Zou; Hanqin Shen; Yongchang Cao; Hao Zhang (Frontiers in Cellular and Infection Microbiology)
The porcine delta coronavirus (PDCoV) is a member of the Delta coronavirus genus, which can lead to diarrhea, vomiting, and mortality in piglets. First detected in Hong Kong in 2012, PDCoV has since spread globally. In January 2024, two strains, CHN-ANHZ-2024 and CHN-JSSQ-2024, were isolated from diarrheal piglets in Anhui and Jiangsu provinces. Immunofluorescence assays, electron microscopy, and genome sequencing were performed. Genome analysis revealed that both PDCoV strains belonged to the Chinese lineage, exhibiting amino acid mutations in the S1 region compared to other strains within the lineage. Amino acid mutation at position 530L is uniquely associated with the Thai strain. Notably, CHN-JSSQ-2024 was identified as a recombinant strain of DH1 and CHN-AHHN-2024, with the recombination occurring in the S2 subunit. CHN-ANHZ-2024 caused severe diarrhea with an 80% mortality rate, whereas CHN-JSSQ-2024 resulted in mild diarrhea without mortality. Viral load analysis showed CHN-ANHZ-2024 primarily infecting the brain and kidneys, while CHN-JSSQ-2024 targeted the lungs, revealing notable differences in tissue tropism. We designed the RNA scope Probe-PDCoV-N to visualize viral RNA in the positively detected organs, viral RNA was detected in the brain, cerebellum, kidneys, and lungs of the infected piglets. This study highlights significant differences in the pathogenicity and organ tropism of two PDCoV strains. The CHN-ANHZ-2024 strain caused severe diarrhea and high mortality in piglets, while the CHN-JSSQ-2024 strain exhibited much milder symptoms. Additionally, the study elucidated notable differences in organ tropism between the strains, offering valuable insights into the epidemiological characteristics and pathogenic mechanisms of PDCoV. These findings provide a foundation for the development of targeted prevention and treatment strategies tailored to specific strains in the future.